Externally-coated composite hydrogel microspheres as well as preparation method and application thereof

By adopting the structure of outer-covered composite hydrogel microspheres in alginate-based sustained-release fertilizer, the hydrogel microsphere core and degradable shell composed of anionic and cationic biological materials is used to solve the problem of waste and encapsulation rate in the fertilizer preparation process in the prior art, and high mechanical performance and controllable sustained-release effect are achieved.

CN119897037AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311397763.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The existing alginate-based sustained-release fertilizers have problems such as waste and difficult to control the encapsulation rate during the preparation process, and poor mechanical properties lead to easy damage during storage, transportation and application, and lose the sustained-release effect.

Method used

The structure of outer-covered composite hydrogel microspheres is adopted, where the core of the hydrogel microsphere is composed of anionic biological material (such as sodium alginate) and cationic biological material (such as starch). The degradable shell is formed through atomization spraying technology to improve mechanical properties and sustained release controllability.

Benefits of technology

It realizes saving raw materials during the processing process, flexibly mixing fertilizer types and content, improves the mechanical properties and controllability of the fertilizers, and solves the problems of prone to sudden release and poor mechanical properties of fertilizers in the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004514250090000161
    Figure BDA0004514250090000161
  • Figure BDA0004514250090000171
    Figure BDA0004514250090000171
  • Figure BDA0004514250090000172
    Figure BDA0004514250090000172
Patent Text Reader

Abstract

The invention discloses an externally-coated composite hydrogel microsphere as well as a preparation method and application thereof. The externally-coated composite hydrogel microsphere comprises a hydrogel microsphere core and a degradable shell, the inner core of the hydrogel microsphere is a mixture and / or a reaction product of components including an anion biological material, a cation biological material, water, a polyhydroxy compound I and multivalent metal salt, and the degradable shell comprises components including a degradable polymer, a plasticizer and a polyhydroxy compound II. The externally-coated composite hydrogel microspheres have a good synergistic effect, the effect of controllable slow release of the fertilizer can be achieved through formula and process blending, the problem that an existing anion biomaterial fertilizer slow-release coating material is prone to burst release is solved, the mechanical performance is good, and the slow-release coating material is suitable for large-scale production. The problem that the slow-release effect is lost due to the fact that anion biological material fertilizer slow-release hydrogel microspheres are prone to being damaged in the processes of storage, transportation, application and the like due to poor mechanical performance is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of slow release, and in particular to slow release of fertilizer, and specifically to an outer-coated composite hydrogel microsphere, and a preparation method and application thereof. Background Art

[0002] Fertilizer, as an important means of production in the agricultural industry, plays a vital role in increasing and maintaining crop yields. However, the use of conventional fertilizers has many environmental problems and disadvantages, such as waste and low efficiency.

[0003] In order to take into account crop production, environmental protection and other aspects, slow-release fertilizers are considered to be one of the effective methods to overcome the shortcomings of conventional fertilizers, and therefore have received great attention, including alginate-based slow-release fertilizers. For example, CN 107903111A discloses a calcium alginate-based slow-release fertilizer encapsulation method, which prolongs the release time of the internal fertilizer; CN 115093288A discloses a sodium alginate water-retaining slow-release fertilizer and a preparation method thereof, which prolongs the effective time of the fertilizer, improves the soil aggregate structure and water retention, and increases crop yields; CN115057741A discloses a preparation method of a non-swelling calcium alginate / chitosan microbead slow-release fertilizer, which improves the swelling resistance in a humid and high-salt environment.

[0004] However, in the prior art, on the one hand, the preparation of alginate-based slow-release fertilizers adopts the method of dissolving the fertilizer in an aqueous solution to directly carry out a cross-linking reaction or heating the fertilizer as an inner core for coating, which is easy to cause waste and difficult to quickly determine the encapsulation rate. The thermal processing conditions limit the types of fertilizers that can be coated; on the other hand, the preparation method of core-shell structure slow-release fertilizers often uses the oil-in-water phase post-precipitation solidification method, and the thickness of the prepared shell is difficult to control, and the emulsifier often plays an important role in the body phase. The use of organic reagents such as emulsifiers and cross-linking agents is not conducive to achieving the purpose of reducing costs, being green and harmless, and being environmentally friendly. The above two aspects greatly limit the further regulation of the slow-release time of fertilizers when facing different crops and fertilization cycles. In addition, the alginate matrix does not have high mechanical strength, which makes it easy to be destroyed and loses its slow-release significance, which limits the further application of alginate as a slow-release fertilizer coating material. Summary of the invention

[0005] In order to overcome the problems existing in the prior art, the present invention provides an outer coated composite hydrogel microsphere and its preparation method and application, wherein, taking the anionic biomaterial selected from sodium alginate and the cationic biomaterial selected from starch as an example, the high water absorption rate of the sodium alginate / starch composite hydrogel microsphere is utilized to perform post-adsorption of the fertilizer solution, so as to save raw materials and flexibly adjust the types and contents of fertilizers during the processing. At the same time, the present invention solves the technical problem that the sodium alginate fertilizer slow-release hydrogel microspheres are easily damaged and lose the slow-release effect during storage, transportation and application due to the poor mechanical properties. After the fertilizer is completely released, the outer shell and internal microspheres of the outer coated composite hydrogel microspheres of the present invention can be naturally degraded as a slow-release carbon source, and can also be composted for secondary use.

[0006] The first aspect of the present invention is to provide an outer coated composite hydrogel microsphere, which includes a composite hydrogel microsphere core and a degradable shell, wherein the hydrogel microsphere core is selected from a mixture and / or reaction product of components including anionic biomaterials, cationic biomaterials, water, polyhydroxy compounds I, and multivalent metal salts.

[0007] The anionic biomaterial is selected from at least one of sodium alginate, carboxymethyl cellulose, polyanionic cellulose, xanthan gum, and guar gum; and / or the cationic biomaterial is selected from at least one of cationically modified starch and chitosan, preferably at least one of cationically modified soybean starch, cationically modified corn starch, cationically modified sweet potato starch, and chitosan.

[0008] The polyol I is selected from at least one of glycerol, hydroxy silicone oil, ethylene glycol, glycerol and sorbitol; and / or,

[0009] The multivalent metal salt is selected from at least one of divalent metal salts, trivalent metal salts, and tetravalent metal salts, preferably at least one of calcium salts, aluminum salts, copper salts, and zinc salts, such as at least one of calcium chloride, aluminum chloride, zinc chloride, aluminum sulfate, and copper sulfate.

[0010] The water content in the inner core of the hydrogel microsphere is 0-10 wt % and preferably does not contain 0, preferably 0-2.5 wt % and more preferably does not contain 0.

[0011] The inner core of the hydrogel microsphere is optionally further loaded with a target slow-release substance, preferably a fertilizer.

[0012] The degradable shell comprises components including a degradable polymer, a plasticizer, and a polyol II; preferably:

[0013] The degradable polymer is at least one selected from polylactic acid, polycaprolactone, polyvinyl alcohol, and polyhydroxyalkanoate. Preferably, the molecular weight of the degradable polymer is 10,000 to 300,000.

[0014] The plasticizer is selected from at least one of polyethylene glycol, glycerol, dibutyl phthalate, tributyl citrate, and epoxidized soybean oil.

[0015] The polyol II is selected from at least one of glycerol, hydroxy silicone oil, ethylene glycol, glycerol and sorbitol.

[0016] In the degradable shell, the weight ratio of the degradable polymer to the plasticizer is (10-15):(3-8).

[0017] The weight ratio of the degradable polymer to the polyhydroxy compound II is (10-15):(1-3).

[0018] The second aspect of the present invention is to provide a method for preparing an outer-coated composite hydrogel microsphere, which is preferably used to prepare the outer-coated composite hydrogel microsphere described in the first aspect of the present invention, and the preparation method comprises: (1) using raw materials including the anionic biomaterial, the cationic biomaterial, water, polyhydroxy compound I, and the multivalent metal salt to prepare the hydrogel microsphere inner core; (2) mixing raw materials including the degradable polymer, the plasticizer, polyhydroxy compound II, and an organic solvent to obtain a degradable shell forming liquid; (3) spraying the degradable shell forming liquid on the surface of the hydrogel microsphere inner core by atomization spraying to form the outer-coated composite hydrogel microsphere.

[0019] In step (1), the weight ratio of the anionic biomaterial to the cationic biomaterial is (1-20):(1-5), preferably (1-10):(1-5), and / or the weight ratio of the cationic biomaterial to the polyhydroxy compound I is (1-10):(1-10), preferably (1-5):(1-5), and / or the weight ratio of the anionic biomaterial to the polyvalent metal salt is (1-10):(10-15).

[0020] After step (1) and before step (2), step (1') is optionally performed: immersing the inner core of the hydrogel microsphere obtained in step (1) in an aqueous solution of the sustained-release target substance; preferably, the concentration of the aqueous solution of the sustained-release target substance is 1 to 99 wt%.

[0021] In step (2), the weight ratio of the degradable polymer to the plasticizer is (10-15):(3-8).

[0022] The weight ratio of the degradable polymer to the polyhydroxy compound II is (10-15):(1-3).

[0023] The organic solvent in step (2) is selected from an organic solvent having a boiling point of 20 to 80° C., preferably at least one of dichloromethane, chloroform, acetone, and ethyl acetate; more preferably, the weight ratio of the degradable polymer to the organic solvent is (10 to 15):(100 to 150).

[0024] The third aspect of the present invention is to provide an application of the outer-coated composite hydrogel microspheres described in one of the purposes of the present invention or the outer-coated composite hydrogel microspheres obtained by the preparation method described in the second purpose of the present invention in the sustained release of a target, especially in the sustained release of fertilizers.

[0025] The outer coated composite hydrogel microspheres of the present invention have good synergistic effects, can achieve the effect of controlled slow release of fertilizers through formulation and process adjustment, can fully coordinate with the crop growth cycle, solve the problem of easy sudden release of existing sodium alginate fertilizer slow-release coating materials, and have good mechanical properties, solve the problem of easy breakage and loss of slow-release effect during storage, transportation and application due to poor mechanical properties of sodium alginate fertilizer slow-release hydrogel microspheres, in addition, a secondary curing method is adopted in the process, and the high water absorption of the composite hydrogel microspheres is used to post-adsorb the fertilizer solution, so as to achieve the purpose of saving raw materials and flexibly adjusting the types and contents of fertilizers in the processing process.

[0026] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The outer-coated composite hydrogel microspheres of the present invention have good mechanical properties. When the sample is compressed radially between two rigid plates, the mechanical properties reach above 100N (especially above 120N);

[0029] (2) The outer coated composite hydrogel microspheres of the present invention have good controllable sustained release. The initial nutrient release rate after immersion in static water at 25°C for 24 hours is less than 15% (preferably less than 5%), the cumulative nutrient release rate after 7 days is less than 30% (preferably less than 15%), and the cumulative nutrient release rate after 28 days is less than 80% (preferably less than 25%). The number of days for the cumulative nutrient release rate to reach 80% can be as long as more than 100 days (preferably more than 120 days and less than 180 days);

[0030] (3) The outer coated composite hydrogel microspheres of the present invention have good synergistic effects, and can achieve the effect of controlled slow release of fertilizers through formulation and process adjustment, thereby solving the problem of easy sudden release of existing anionic biomaterial (such as sodium alginate) fertilizer slow-release coating materials. The microspheres have good mechanical properties, thereby solving the problem of easy breakage and loss of slow-release effect during storage, transportation and application due to poor mechanical properties of anionic biomaterial (such as sodium alginate) fertilizer slow-release hydrogel microspheres. In addition, the high water absorption of the composite hydrogel microspheres is used to post-adsorb the fertilizer solution in the process, so as to save raw materials and flexibly adjust the types and contents of fertilizers during the processing. DETAILED DESCRIPTION

[0031] One of the purposes of the present invention is to provide an outer-coated composite hydrogel microsphere, which comprises a hydrogel microsphere core and a degradable shell.

[0032] In a preferred embodiment, the inner core of the hydrogel microsphere is selected from a mixture and / or reaction product of components including anionic biomaterials, cationic biomaterials, water, polyhydroxy compounds I, and multivalent metal salts.

[0033] In a preferred embodiment, the anionic biomaterial is selected from at least one of sodium alginate, carboxymethyl cellulose, polyanionic cellulose, xanthan gum, and guar gum; and / or the cationic biomaterial is selected from at least one of cationically modified starch (e.g., water-soluble starch) and chitosan, preferably at least one of cationically modified soybean starch, cationically modified corn starch, cationically modified sweet potato starch, and chitosan.

[0034] In a preferred embodiment, the anionic biomaterial is selected from one or a combination of low-viscosity anionic biomaterials, medium-viscosity anionic biomaterials, and high-viscosity anionic biomaterials. The viscosity of the low-viscosity anionic biomaterial is 1 to 20 mPa·s, preferably 3 to 5 mPa·s, the viscosity of the medium-viscosity anionic biomaterial is 100 to 800 mPa.s, preferably 200 to 400 mPa.s, and the viscosity of the high-viscosity anionic biomaterial is 3000 to 15000 mPa.s, preferably 5000 to 10000 mPa.s.

[0035] Among them, the viscosity of the low-viscosity anionic biomaterial is 3, 3.5, 4, 4.5 or 5 mPa·s, the viscosity of the medium-viscosity anionic biomaterial is 200, 250, 300, 350 or 400 mPa.s, and the viscosity of the high-viscosity anionic biomaterial is 5000, 6000, 7000, 8000, 9000 or 10000 mPa.s.

[0036] In a further preferred embodiment, the anionic biomaterial is selected from a combination of one or both of a medium-viscosity anionic biomaterial and / or a high-viscosity anionic biomaterial and a low-viscosity anionic biomaterial.

[0037] In a further preferred embodiment, the weight ratio of one or both of the medium-viscosity anionic biomaterial and / or the high-viscosity anionic biomaterial to the low-viscosity anionic biomaterial is (1-20):1, preferably (1-10):1, for example, 1:1, 2:1, 4:1, 6:1, 8:1, 10:1, 12:1, 14:1, 16:1, 18:1 or 20:1.

[0038] In a preferred embodiment, the polyhydroxy compound I is selected from at least one of glycerol, hydroxy silicone oil, ethylene glycol, glycerol, and sorbitol.

[0039] The polyhydroxy compound is beneficial to the plasticization or gelatinization of cationic biomaterials (such as cationic starch).

[0040] In a preferred embodiment, the multivalent metal salt is selected from at least one of a divalent metal salt, a trivalent metal salt, and a tetravalent metal salt, preferably at least one of a calcium salt, an aluminum salt, a copper salt, and a zinc salt, such as at least one of calcium chloride, aluminum chloride, zinc chloride, aluminum sulfate, and copper sulfate.

[0041] The primary curing is carried out between the cationic biomaterial and the anionic biomaterial, and the secondary curing is further physically cross-linked with the anionic biomaterial under the action of the multivalent metal salt.

[0042] In a preferred embodiment, the inner core of the hydrogel microsphere is prepared using raw materials including the anionic biomaterial, the cationic biomaterial, water, the polyhydroxy compound I, and the multivalent metal salt.

[0043] In a further preferred embodiment, the weight ratio of the anionic biomaterial to the cationic biomaterial is (1-20):(1-5), preferably (1-10):(1-5), and / or the weight ratio of the cationic biomaterial to the polyhydroxy compound I is (1-10):(1-10), preferably (1-5):(1-5), and / or the weight ratio of the anionic biomaterial to the polyvalent metal salt is (1-10):(10-15).

[0044] For example, the weight ratio of the anionic biomaterial to the cationic biomaterial is (1, 2, 4, 6, 8 or 10): (1, 2, 3, 4 or 5), the weight ratio of the cationic biomaterial to the polyhydroxy compound I is (1, 2, 3, 4 or 5): (1, 2, 3, 4 or 5), and the weight ratio of the anionic biomaterial to the polyvalent metal salt is (1, 2, 4, 6, 8 or 10): (10, 11, 12, 13, 14 or 15).

[0045] In a preferred embodiment, the water content in the inner core of the hydrogel microsphere is 0-10wt%, preferably 0-2.5wt%, and more preferably does not contain 0.

[0046] For example, the water content in the inner core of the hydrogel microsphere is 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.

[0047] In a preferred embodiment, the inner core of the hydrogel microsphere is optionally further loaded with a target slow-release substance, such as a fertilizer.

[0048] In a further preferred embodiment, the fertilizer is a component that can provide plant nutrients, including but not limited to at least one of nitrogen fertilizer, phosphorus fertilizer, potassium fertilizer, boron fertilizer, molybdenum fertilizer, manganese fertilizer, copper fertilizer, iron fertilizer, zinc fertilizer, and biological fertilizer.

[0049] In a preferred embodiment, based on 100wt% of the hydrogel microsphere inner core, the target sustained-release substance loaded therein is 5-50wt%, preferably 10-30wt%, for example 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%.

[0050] In a preferred embodiment, the degradable shell includes components including a degradable polymer, a plasticizer, and a polyol II.

[0051] In a preferred embodiment, the degradable polymer is selected from at least one of polylactic acid, polycaprolactone, polyvinyl alcohol and polyhydroxyalkanoate.

[0052] In a further preferred embodiment, the molecular weight of the degradable polymer is 10,000 to 300,000, for example, 10,000, 50,000, 100,000, 150,000, 200,000, 250,000 or 300,000.

[0053] After a large number of experimental studies, the inventors found that when the molecular weight of the degradable polymer is lower than 10,000, the mechanical properties of the obtained outer-coated composite hydrogel microspheres are poor. When the molecular weight of the degradable polymer exceeds 300,000, although the mechanical properties are better, its degradation cycle is too long, which is not conducive to the application of fertilizers in the actual production process.

[0054] In a preferred embodiment, the plasticizer is selected from at least one of polyethylene glycol, glycerol, dibutyl phthalate, tributyl citrate, and epoxy soybean oil; and / or the polyhydroxy compound II is selected from at least one of glycerol, hydroxy silicone oil, ethylene glycol, glycerol, and sorbitol.

[0055] Wherein, the polyethylene glycol is selected from at least one of polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600 and polyethylene glycol 800.

[0056] In a preferred embodiment, in the degradable shell, the weight ratio of the degradable polymer to the plasticizer is (10-15):(3-8); and / or the weight ratio of the degradable polymer to the polyol II is (10-15):(1-3).

[0057] For example, in the degradable shell, the weight ratio of the degradable polymer to the plasticizer is (10, 11, 12, 13, 14 or 15):(3, 4, 5, 6, 7 or 8); and / or, the weight ratio of the degradable polymer to the polyol II is (10, 11, 12, 13, 14 or 15):(1, 2 or 3).

[0058] Among them, since the degradable shell is obtained in the form of spray, the content of each component in the degradable shell product is the same as the amount of raw materials, except for organic solvents, because organic solvents will evaporate during the spraying process, after spraying and during subsequent placement.

[0059] In a preferred embodiment, the thickness of the degradable shell is 10-20 μm, for example, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm.

[0060] Among them, after a lot of experimental research, the inventors found that controlling the thickness of the degradable shell within the above range can effectively control the sustained release degree of the target sustained release substance, especially the initial sustained release degree. Specifically, the initial sustained release degree can be controlled to be lower, and the number of days when the release reaches 80% can be longer.

[0061] The second object of the present invention is to provide a method for preparing an outer-coated composite hydrogel microsphere, comprising: (1) preparing a hydrogel microsphere inner core by mixing raw materials including the anionic biomaterial, the cationic biomaterial, water, polyhydroxy compound I, and the multivalent metal salt; (2) mixing raw materials including the degradable polymer, the plasticizer, polyhydroxy compound II, and an organic solvent to obtain a degradable shell forming liquid; and (3) spraying the degradable shell forming liquid onto the surface of the hydrogel microsphere inner core by atomizing spraying to form the outer-coated composite hydrogel microsphere.

[0062] In a preferred embodiment, in step (1), the weight ratio of the anionic biomaterial to the cationic biomaterial is (1-10):(1-5), and / or the weight ratio of the cationic biomaterial to the polyhydroxy compound I is (1-5):(1-5), and / or the weight ratio of the anionic biomaterial to the polyvalent metal salt is (1-10):(10-15).

[0063] For example, in step (1), the weight ratio of the anionic biomaterial to the cationic biomaterial is (1, 2, 4, 6, 8 or 10): (1, 2, 3, 4 or 5), and / or the weight ratio of the cationic biomaterial to the polyhydroxy compound I is (1, 2, 3, 4 or 5): (1, 2, 3, 4 or 5), and / or the weight ratio of the anionic biomaterial to the polyvalent metal salt is (1, 2, 4, 6, 8 or 10): (10, 11, 12, 13, 14 or 15).

[0064] In a preferred embodiment, step (1) comprises: (1.1) preparing an aqueous solution I of the anionic biomaterial, preparing an aqueous solution II of the cationic biomaterial and the polyhydroxy compound I, and preparing an aqueous solution III of the polyvalent metal salt; (1.2) mixing the aqueous solution I with the aqueous solution II to obtain a mixed solution, stirring, standing, and filtering to obtain preliminary microspheres; (1.3) (preferably under slow stirring) adding the preliminary microspheres to the aqueous solution III, collecting the microspheres after cross-linking and curing, and freeze-drying to obtain the hydrogel microsphere inner core.

[0065] In a further preferred embodiment, in step (1.1), the aqueous solution I of the anionic biomaterial is obtained as follows: the anionic biomaterial is mixed with water, stirred to completely dissolve it; and / or, the aqueous solution II of the cationic biomaterial and the polyhydroxy compound I is obtained as follows: the cationic biomaterial is mixed with water, gelatinized at 50-90°C (preferably 65-75°C), and the polyhydroxy compound is added and continued to stir.

[0066] The aqueous solution I of the anionic biomaterial is obtained as follows: the anionic biomaterial is dissolved in water, and mechanically stirred for 60 to 300 minutes at a stirring speed of 60 to 100 r / min to completely dissolve it. The aqueous solution II of the cationic biomaterial and the polyhydroxy compound I is obtained as follows: the cationic biomaterial is dissolved in water, and the cationic biomaterial is gelatinized in a boiling distilled water bath at 50 to 90° C. (preferably 65 to 75° C.), and after adding the polyhydroxy compound I, mechanical stirring is continued for 30 to 60 minutes at a stirring speed of 100 to 150 r / min.

[0067] Preferably, when preparing the aqueous solution I of the anionic biomaterial, the weight ratio of the anionic biomaterial to water is 1:(10-100), preferably 1:(10-50). When preparing the aqueous solution II of the cationic biomaterial and the polyhydroxy compound I, the weight ratio of the cationic biomaterial to water is 1:(50-200), preferably 1:(50-100).

[0068] For example, when preparing the aqueous solution I of the anionic biomaterial, the weight ratio of the anionic biomaterial to water is 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 or 1:100. When preparing the aqueous solution II of the cationic biomaterial and the polyol I, the weight ratio of the cationic biomaterial to water is 1:50, 1:60, 1:80, 1:100, 1:120, 1:140, 1:160, 1:180 or 1:200.

[0069] In a further preferred embodiment, the freeze-drying in step (1.3) is carried out by gradient cooling.

[0070] Optionally, the gradient freeze drying specifically includes the following steps: primary freezing: at normal pressure, the temperature is -40°C to -30°C, and the freezing time is 1 to 2 hours; primary freeze drying: at normal pressure, the temperature is -40°C to -30°C, and the freezing time is 6 to 12 hours. Secondary freezing: at normal pressure, the temperature is -80°C to -70°C, and the freezing time is 12 to 24 hours; secondary freeze drying: at normal pressure, the temperature is -60°C to -50°C, and the freezing time is 1 to 2 hours.

[0071] For example, the gradient freeze drying specifically comprises the following steps: primary freezing: at normal pressure, at a temperature of -40°C, -38°C, -36°C, -34°C, -32°C or -30°C, for a freezing time of 1, 1.2, 1.4, 1.6, 1.8 or 2 hours; primary freeze drying: at normal pressure, at a temperature of -40°C, -38°C, -36°C, -34°C, -32°C or -30°C, for a freezing time of 6, 7, 8, 9, 10, 11 or 12 hours; secondary freezing: at normal pressure, the temperature is -80°C, -78°C, -76°C, -74°C, -72°C or -70°C, and the freezing time is 12, 14, 16, 18, 20, 22 or 24 hours; secondary freeze drying: at normal pressure, the temperature is -60°C, -58°C, -56°C, -54°C, -52°C or -50°C for freezing and drying, and the time is 1, 1.2, 1.4, 1.6, 1.8 or 2 hours. In a preferred embodiment, after step (1) and before step (2), step (1') is optionally performed: the inner core of the hydrogel microsphere obtained in step (1) is immersed in an aqueous solution of the sustained-release target substance.

[0072] The inner core of the microsphere is immersed in an aqueous solution of the sustained-release target substance to allow it to absorb and swell. After the swelling and absorption are complete, the inner core of the microsphere is taken out, the surface is rinsed with water, and then dried.

[0073] In a further preferred embodiment, the concentration of the sustained-release target aqueous solution is 1 to 99wt%, for example, 1wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 99wt%.

[0074] In a further preferred embodiment, the weight ratio of the sustained-release target aqueous solution to the hydrogel microsphere inner core of step (1) is (1-100):1, for example, 1:1, 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1 or 100:1.

[0075] In a preferred embodiment, in step (2), the weight ratio of the degradable polymer to the plasticizer is (10-15):(3-8); and / or the weight ratio of the degradable polymer to the polyol II is (10-15):(1-3).

[0076] In a preferred embodiment, the organic solvent in step (2) is selected from organic solvents having a boiling point of 20 to 80° C., preferably at least one of dichloromethane, chloroform, acetone and ethyl acetate.

[0077] In a further preferred embodiment, the weight ratio of the degradable polymer to the organic solvent is (10-15):(100-150), for example, (10, 11, 12, 13, 14 or 15):(100, 110, 120, 130, 140 or 150).

[0078] In a preferred embodiment, in step (3), the thickness of the sprayed degradable shell is controlled to be 10-20 μm, for example, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm.

[0079] The preparation method of the present invention does not need to be carried out in a dry high-temperature environment, does not require a filter, extrusion granulation, etc., reduces the loss of fertilizers in the process and expands the types of optional fertilizers, and is easy to determine the fertilizer encapsulation rate.

[0080] The preparation method of the present invention has two curing processes. The first curing is carried out between the anionic and cationic biomaterials to enhance the water absorption rate of the materials. The second curing uses multivalent metal salts to further physically cross-link and reinforce the appearance. The entire preparation does not require a high-temperature dry environment, and does not require filters, extrusion granulation, etc., which reduces the loss of fertilizers in the process and expands the types of optional fertilizers.

[0081] The preparation method may include:

[0082] Step A: Dissolve the anionic biomaterial in water and stir it mechanically to dissolve it completely.

[0083] Step B: Dissolve the cationic biomaterial in water and change the method to make the solution uniform according to different materials (for example, add polyol I).

[0084] Step C: drip the cationic biomaterial solution prepared in step B into the anionic biomaterial solution in step A and stir. After stirring evenly, pour into a beaker, let stand, and filter to obtain preliminary microspheres.

[0085] Step D: Prepare a polyvalent metal solution using water, add the preliminary microspheres obtained in step C to the polyvalent metal solution under low-speed stirring conditions, collect the microspheres after cross-linking and solidification, and perform gradient cooling and freeze-drying to obtain the microsphere cores.

[0086] Step E: dissolving the target sustained-release substance such as urea in water to prepare a target sustained-release aqueous solution, immersing the microsphere core obtained in step D in the target sustained-release aqueous solution to allow it to absorb and swell, taking it out after complete swelling and absorption, washing the surface with water, and drying it at room temperature.

[0087] Step F: using an organic solvent to dissolve the degradable polymer, the plasticizer, and the polyol II to prepare a degradable shell layer forming liquid.

[0088] Step G: Ultrasonic atomization spraying equipment is used to evenly spray the degradable shell-forming liquid in step F onto the surface of the microspheres prepared in step E to thicken the surface, thereby obtaining composite hydrogel microspheres coated with controlled-release fertilizer.

[0089] The third object of the present invention is to provide the use of the outer-coated composite hydrogel microspheres described in the first object of the present invention or the outer-coated composite hydrogel microspheres obtained by the preparation method described in the second object of the present invention in the sustained release of the target object, especially in the sustained release of fertilizers.

[0090] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0091] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0092] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0093] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0094] [Example 1]

[0095] Step A: Dissolve 7 parts by weight of sodium alginate with different viscosities (5 mPa·s: 5000 mPa·s: 7000 mPa·s = 4:2:1) in 100 parts of deionized water, and stir mechanically for 180 min at a stirring speed of 90 r / min to completely dissolve the alginate.

[0096] Step B: Dissolve 1 part by weight of cationic modified soybean starch in 100 parts of deionized water, gelatinize the starch in a boiling distilled water bath at 70° C., add 1 part by weight of glycerol, and continue mechanical stirring for 30 minutes at a stirring speed of 100 r / min.

[0097] Step C: Add the prepared cationic modified soybean starch solution in step B to the sodium alginate solution in step A, and stir for 30 minutes at a stirring speed of 50 r / min. After stirring evenly, pour into a beaker, let stand for 15 minutes, and filter to obtain preliminary microspheres.

[0098] Step D: 15 parts of calcium chloride are added to 100 parts by weight of deionized water to prepare a calcium chloride solution. Under low-speed stirring conditions, the preliminary microspheres obtained in step C are added to the calcium chloride solution. After cross-linking and curing, the microspheres are collected and freeze-dried by gradient cooling: at normal pressure, at a temperature of -40°C, for 2 hours; primary freeze-drying: at normal pressure, at a temperature of -30°C, for 6 hours. Secondary freezing: at normal pressure, at a temperature of -70°C, for 12 hours; secondary freeze-drying: at normal pressure, at a temperature of -50°C, for 2 hours.

[0099] Step E: Dissolve urea in deionized water to prepare a 90 wt% aqueous solution, soak the microspheres obtained in step D in the fertilizer solution to allow them to absorb and swell (the mass ratio of microspheres to fertilizer solution is 1:5), take them out after complete swelling and absorption, rinse the surface with deionized water, and dry them at room temperature for 24 hours to obtain the microsphere core.

[0100] Based on 100 wt % of the microsphere inner core, it contains 2 wt % of water and 18 wt % of urea.

[0101] Step F: 15 parts by weight of polylactic acid (molecular weight 100,000), 5 parts by weight of polyethylene glycol 400, and 3 parts by weight of glycerol are dissolved in 100 parts by weight of dichloromethane to prepare a degradable polymer solution.

[0102] Step G: The degradable polymer solution in step F is evenly sprayed on the surface of the microsphere inner core prepared in step E by ultrasonic atomization spraying equipment, with a coating thickness of 10 μm, to obtain controlled-release fertilizer-coated composite hydrogel microspheres.

[0103] [Example 2]

[0104] Repeat steps A to F in Example 1;

[0105] Step G: Ultrasonic atomization spraying equipment is used to evenly spray the degradable polymer solution in step F onto the surface of the sodium alginate / starch composite hydrogel microspheres prepared in step E, with a coating thickness of 20 μm, to obtain the above-mentioned controlled-release fertilizer-coated composite hydrogel microspheres.

[0106] [Example 3]

[0107] The process of Example 1 was repeated, except that 7 parts by weight of sodium alginate (viscosity 5 mPa·s) was used, and other conditions were the same as in Example 1.

[0108] [Example 4]

[0109] The process of Example 1 was repeated, except that 7 parts by weight of sodium alginate (viscosity 5000 mPa·s) was used, and other conditions were the same as in Example 1.

[0110] [Example 5]

[0111] The process of Example 1 was repeated, except that 7 parts by weight of sodium alginate (viscosity 7000 mPa·s) was used, and other conditions were the same as Example 1. During the process, it was found that the viscosity of the system was too high, dissolution and reaction were difficult, and it was impossible to prepare smoothly according to the steps.

[0112] [Example 6]

[0113] The process of Example 1 was repeated, except that 2 parts by weight of cationic modified soybean starch was dissolved in 100 parts of deionized water, and other conditions were the same as in Example 1.

[0114] [Example 7]

[0115] The process of Example 1 was repeated, except that 5 parts by weight of cationic modified soybean starch was dissolved in 100 parts of deionized water, and other conditions were the same as in Example 1.

[0116] [Example 8]

[0117] Repeat steps A to F in Example 1;

[0118] Step G: Ultrasonic atomization spraying equipment is used to evenly spray the degradable polymer solution in step F onto the surface of the sodium alginate / starch composite hydrogel microspheres prepared in step E, with a coating thickness of 5 μm, to obtain the above-mentioned controlled-release fertilizer-coated composite hydrogel microspheres.

[0119] [Example 9]

[0120] Repeat steps A to F in Example 1;

[0121] Step G: Ultrasonic atomization spraying equipment is used to evenly spray the degradable polymer solution in step F onto the surface of the sodium alginate / starch composite hydrogel microspheres prepared in step E, with a coating thickness of 30 μm, to obtain the above-mentioned controlled-release fertilizer-coated composite hydrogel microspheres.

[0122] [Comparative Example 1]

[0123] The difference from Example 1 is that the molecular weight of the polylactic acid is 10,000. Other conditions are the same.

[0124] [Comparative Example 2]

[0125] The difference from Example 1 is that the core does not contain starch or glycerol. During the implementation process, it was found that the fertilizer solution could not be completely absorbed, and the encapsulation rate was determined by the remaining amount and concentration of the fertilizer solution, and the actual encapsulation rate was used as the initial concentration of the slow release. Other conditions were the same.

[0126] [Comparative Example 3]

[0127] The difference from Example 1 is that the degradable polymer is not used for external coating. Other conditions are the same.

[0128] [Comparative Example 4]

[0129] The difference from Example 1 is that the core does not contain starch or glycerol and is not coated with a degradable polymer. During the implementation process, it was found that the fertilizer solution could not be completely absorbed, and the encapsulation rate was calculated based on the remaining mass of the fertilizer solution. Other conditions were the same.

[0130] [Comparative Example 5]

[0131] The difference from Example 1 is that 10 parts of calcium chloride and 100 parts of deionized water are used to prepare the calcium chloride solution, and no degradable polymer coating is used. Other conditions are the same.

[0132]

Test Example 1

[0133] Samples with a particle size between 3 and 5 mm were screened for the products of the examples and comparative examples, and the mechanical properties of the samples were tested using a texture analyzer. Each sample was compressed radially between two rigid plates, and 20 samples of the same type were tested to obtain the average mechanical strength. The results are shown in Table 1 below.

[0134] Table 1

[0135]

[0136]

Test Example 2

[0137] The slow-release fertilizer test was carried out on the products obtained in the examples and comparative examples with reference to the national standard in GB / T 23348-2009: under static water conditions at 25°C, the fertilizer nutrient release period was tested by water immersion method. If the cumulative nutrient release after 28 days still did not reach 80%, the days when the cumulative nutrient release reached 80% were listed. For the convenience of comparison, the urea granules used were tested as samples. The results are shown in Table 2 below.

[0138] If the fertilizer solution is not completely absorbed, the encapsulation rate is determined by the remaining amount of the fertilizer solution, and the actual encapsulation rate is used as the initial concentration of the slow release. The urea content of the remaining fertilizer solution is determined by the Kjeldahl method, and the actual encapsulation rate is further determined. The urea content of the remaining fertilizer solution after absorption is calculated as its mass fraction w, and the value is expressed in %, and is calculated as follows:

[0139]

[0140] Where: v0 is the volume of hydrochloric acid standard solution consumed in blank; v1 is the volume of sodium hydroxide standard titration solution consumed by the sample during determination; c is the concentration of sodium hydroxide standard titration solution used; m is the sample volume. x is the conversion factor between nitrogen content and urea.

[0141] The absorbed fertilizer solution, i.e. the actual encapsulation rate, is expressed in AE and is calculated as follows:

[0142]

[0143] Wherein: M2 is the mass of the fertilizer solution remaining after absorption, w is the mass fraction of urea in the fertilizer remaining after absorption, M1 is the mass of the fertilizer solution before absorption, and W is the mass fraction of urea in the fertilizer solution before absorption.

[0144] Table 2:

[0145]

[0146]

[0147] As can be seen from Table 1, the mechanical properties of the samples without outer shell coating are poor, while the mechanical properties of the samples after outer shell coating are mainly affected by the thickness and molecular weight of the polymer shell. As can be seen from Table 2, the nutrient release rate of urea granules is relatively fast, and the nutrient release rate can be significantly reduced after outer coating. Many samples have reached the standard of less than 15% (preferably less than 5%) of the initial nutrient release rate after soaking in 25°C static water for 24 hours, and less than 70% (preferably less than 25%) of the cumulative nutrient release rate in 28 days. Among them, Example 1, Example 2, Example 6, and Example 7 have good slow-release effect and mechanical properties, while the slow-release effect and mechanical properties of Comparative Example 4 using only sodium alginate core are poor. In addition, it was found during the experiment that the nutrient release rate of the polymer shell is faster, especially in the middle and late stages, compared with the high molecular weight; the shell thickness has a greater influence on the nutrient release rate, and too low or too high thickness is not conducive to matching the common crop growth cycle; it can be seen from Comparative Example 2 that if starch is not contained, it will significantly affect the absorption efficiency of the fertilizer solution in the preparation process and affect the nutrient release efficiency. In summary, the effect of controlled sustained release can be achieved by changing the raw material ratio and the polylactic acid spraying thickness.

[0148] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. An outer coated composite hydrogel microsphere, comprising a hydrogel microsphere core and a degradable shell, wherein the hydrogel microsphere core is selected from a mixture and / or reaction product of components including anionic biomaterials, cationic biomaterials, water, polyhydroxy compounds I, and multivalent metal salts.

2. The outer-coated composite hydrogel microsphere according to claim 1, characterized in that: The anionic biomaterial is selected from at least one of sodium alginate, carboxymethyl cellulose, polyanionic cellulose, xanthan gum, and guar gum; and / or the cationic biomaterial is selected from at least one of cationically modified starch and chitosan, preferably at least one of cationically modified soybean starch, cationically modified corn starch, cationically modified sweet potato starch, and chitosan.

3. The outer-coated composite hydrogel microsphere according to claim 1, characterized in that: The polyol I is selected from at least one of glycerol, hydroxy silicone oil, ethylene glycol, glycerol and sorbitol; and / or, The multivalent metal salt is selected from at least one of divalent metal salts, trivalent metal salts, and tetravalent metal salts, and is preferably selected from at least one of calcium salts, aluminum salts, copper salts, and zinc salts.

4. The outer-coated composite hydrogel microsphere according to claim 1, characterized in that: The water content in the inner core of the hydrogel microsphere is 0 to 10 wt%, preferably 0 to 2.5 wt%; and / or, The inner core of the hydrogel microsphere is optionally further loaded with a target slow-release substance, preferably a fertilizer.

5. The outer-coated composite hydrogel microsphere according to claim 1, characterized in that: The degradable shell comprises components including a degradable polymer, a plasticizer, and a polyol II; preferably: The degradable polymer is selected from at least one of polylactic acid, polycaprolactone, polyvinyl alcohol and polyhydroxyalkanoate, and preferably the molecular weight of the degradable polymer is 10,000 to 300,000; and / or, The plasticizer is selected from at least one of polyethylene glycol, glycerol, dibutyl phthalate, tributyl citrate, and epoxidized soybean oil; and / or, The polyhydroxy compound II is selected from at least one of glycerol, hydroxy silicone oil, ethylene glycol, glycerol and sorbitol.

6. The outer-coated composite hydrogel microsphere according to claim 5, characterized in that: In the degradable shell, the weight ratio of the degradable polymer to the plasticizer is (10-15):(3-8); and / or, The weight ratio of the degradable polymer to the polyhydroxy compound II is (10-15):(1-3).

7. A method for preparing an outer-coated composite hydrogel microsphere, preferably used to prepare the outer-coated composite hydrogel microsphere according to any one of claims 1 to 6, the preparation method comprising: (1) preparing a hydrogel microsphere inner core by mixing raw materials including the anionic biomaterial, the cationic biomaterial, water, polyhydroxy compound I, and the multivalent metal salt; (2) mixing raw materials including the degradable polymer, the plasticizer, polyhydroxy compound II, and an organic solvent to obtain a degradable shell forming liquid; (3) spraying the degradable shell forming liquid onto the surface of the hydrogel microsphere inner core by atomizing spraying to form the outer-coated composite hydrogel microsphere.

8. The preparation method according to claim 7, characterized in that: In step (1), the weight ratio of the anionic biomaterial to the cationic biomaterial is (1-20):(1-5), preferably (1-10):(1-5), and / or the weight ratio of the cationic biomaterial to the polyhydroxy compound I is (1-10):(1-10), preferably (1-5):(1-5), and / or the weight ratio of the anionic biomaterial to the polyvalent metal salt is (1-10):(10-15).

9. The preparation method according to claim 7, characterized in that: After step (1) and before step (2), step (1') is optionally performed: immersing the inner core of the hydrogel microsphere obtained in step (1) in an aqueous solution of the sustained-release target substance; preferably, the concentration of the aqueous solution of the sustained-release target substance is 1 to 99 wt%.

10. The preparation method according to any one of claims 7 to 9, characterized in that: In step (2), the weight ratio of the degradable polymer to the plasticizer is (10-15):(3-8); and / or, The weight ratio of the degradable polymer to the polyol II is (10-15):(1-3); and / or, The organic solvent in step (2) is selected from an organic solvent having a boiling point of 20 to 80° C., preferably at least one of dichloromethane, chloroform, acetone, and ethyl acetate; more preferably, the weight ratio of the degradable polymer to the organic solvent is (10 to 15):(100 to 150).

11. Use of the outer-coated composite hydrogel microspheres according to any one of claims 1 to 6 or the outer-coated composite hydrogel microspheres obtained by the preparation method according to any one of claims 7 to 10, preferably in the sustained release of a target, more particularly in the sustained release of a fertilizer.

Citation Information

Patent Citations

  • Preparation method of natural-polymer-based slow-release fertilizer

    CN107903111A

  • Preparation method of calcium alginate-chitosan microsphere slow-release fertilizer not easy to swell

    CN115057741A

  • Alginic acid water-retaining slow-release fertilizer and preparation method thereof

    CN115093288A

  • Anti-bioadhesion polyelectrolyte gel as well as preparation method and application thereof

    CN107753421A

  • Goserelin sustained release microsphere freeze-dried powder and preparation method thereof

    CN109394705A

Cited By

  • Multilayer controllable degradation coating composition as well as preparation method and application thereof

    CN120442137A